2011
DOI: 10.1186/1477-7827-9-131
|View full text |Cite
|
Sign up to set email alerts
|

The promoter -1031(T/C) polymorphism in tumor necrosis factor-alpha associated with polycystic ovary syndrome

Abstract: BackgroundA tumor necrosis factor-alpha is a multifunctional pro-inflammation cytokine, which has been considered as one of pathogenic factors for various diseases. The promoter -1031(T/C) polymorphism in the tumor necrosis factor-alpha gene was reported that it plays a part in reproduction-related diseases. Among these, polycystic ovary syndrome (PCOS) is known to be a common gynecological disease of women in reproductive age women. Here, we performed a comparative study of -1031(T/C) polymorphism of TNF-alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 42 publications
7
39
0
Order By: Relevance
“…Eight publications were excluded for insufficient or uncorrelated data according to our inclusion criteria [9,11,10,14,13,23,24,30]. Finally, 18 articles met the inclusion criteria and were selected [8,7,27,12,28,18,15,17,20,19,22,21,25,26,29,31,16]. The study selection process is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight publications were excluded for insufficient or uncorrelated data according to our inclusion criteria [9,11,10,14,13,23,24,30]. Finally, 18 articles met the inclusion criteria and were selected [8,7,27,12,28,18,15,17,20,19,22,21,25,26,29,31,16]. The study selection process is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…For -805C>T, 87 cases and 115 controls were analyzed from the study by Korhonen [29]. Finally, for the -1031 T>C polymorphism, 500 PCOS cases and 450 controls from 2 articles were included [28,27].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The aetiology of PCOS is not yet clear however genetic, biochemical, immunological and environmental factors are implicated in the aetiopathogeneis of this multifactorial condition [3]. Several candidate genes have been proposed as important contributors to PCOS but none have yet achieved acceptance as major cause [4]. Janine et al, (2001) suggested the involvement of cytokines as regulatory factors in follicular development in ovary and the frequently studied cytokine in the ovary is Tumor Necrosis Factor alpha (TNF-α) [5].…”
Section: Introductionmentioning
confidence: 99%
“…SNPs in TNF-α with PCOS, such as -1031 T>C (rs1799964) and rs1800629 in promoter region of TNF-α (Yun et al 2011;Deepika et al 2013Deepika et al , 2016. The SNP rs1799964 has been linked with altered promoter activity leading to varied plasma TNF-α levels in healthy subjects and repeatedly reported to be significantly associated with PCOS (Yun et al 2011;Deepika et al 2013Deepika et al , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP rs1799964 has been linked with altered promoter activity leading to varied plasma TNF-α levels in healthy subjects and repeatedly reported to be significantly associated with PCOS (Yun et al 2011;Deepika et al 2013Deepika et al , 2016. Unfortunately, the various association studies on rs1800629 have obtained conflicting results due to their relative small sample size (Deepika et al 2013;Kume et al 2016).…”
Section: Discussionmentioning
confidence: 99%